An evaluation of physical and mechanical scarification methods on seed germination of Vachellia macracantha (Humb. and Bonpl. ex Willd.) Seigler and Ebinger (2018)
The dry Andean forests are ecosystems with a high diversity of flora and fauna and are at high risk of extinction due to the pressure of human activity. V. macracantha is a native species of the dry Andean forest, which has potential for reforestation and also provides benefits in agroforestry systems, due to its nitrogen fixation capacity, the supply of organic matter, the production of shade and wind protection. The multiplication of this species is limited due to the low percentage of seed germination, which present dormancy. The aim of this research was to determine the most effective scarification method for seeds germination of V. macracantha. Two types of methods were tested, the immersion in strong acids (chemical scarification), and the seed bark through filing, cutting and soaking into hot water (physical scarification). A completely randomized block design with 3 replicates was used. For the chemical methods, sulfuric, nitric, and phosphoric acid (50% v/v) were used at different exposure times: 5, 10, 15, 20 and 25 minutes, respectively. Three variables were measured as follows: percentage of germination, the number of leaves and the plant height. The chemical methods did not present any significant difference in the percentage of germination. The physical method of seed filing, had achieved the highest percentage of germination with 46%, compared to control treatment, which had achieved 6%. No treatment performed significant differences in the parameters of number of leaves and plant height.